2015
DOI: 10.5551/jat.27789
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Partially Suppresses Inflammatory Events but Does not Affect Stroke Onset in Stroke-Prone Spontaneously Hypertensive Rats

Abstract: Aim:Resveratrol has been shown to mimic the beneficial effects of dietary restriction (DR). We previously reported that DR delays stroke onset and extends the lifespan in Stroke-Prone Spontaneously Hypertensive rats (SHRSP). Therefore, we examined whether resveratrol mimics DR and delays stroke onset in SHRSP. Methods: Cerebrovascular endothelial cells (CVECs) from SHRSP were treated with resveratrol, and the inflammatory gene expression levels and NF B protein levels were measured. In order to address the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…After removing duplicate and not relevant records, 90 full-text articles and one congress abstract were assessed for eligibility. Reasoned exclusions (16 studies) 18 33 rendered 75 studies included in the qualitative synthesis, 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicate and not relevant records, 90 full-text articles and one congress abstract were assessed for eligibility. Reasoned exclusions (16 studies) 18 33 rendered 75 studies included in the qualitative synthesis, 34 …”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicate and not relevant records, 90 full-text articles and one congress abstract were assessed for eligibility. Reasoned exclusions (16 studies) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] rendered 75 studies included in the qualitative synthesis, and further exclusions (18 studies) 36,43,44,46,56,61,64,65,69,76,78,83,92,93,98,103,104,107 resulted in 57 studies subjected to meta-analysis of seven stroke outcomes. 34,35,37-42,45,47-55,57-60,62,63,66-68, 70-75,77,79-82,84-91,94-97,99-102,105,106,108…”
Section: Literature Searchmentioning
confidence: 99%
“…92 In addition, 0.0% resveratrol exerts a marginally inhibitory effect on serum IL-1b and monocyte chemotactic protein 1 levels, which are involved in inflammation in SHRSP. 93 In addition, experiments using aorta specimens isolated from SHRs showed that resveratrol induced calciumdependent endothelial NO synthase phosphorylation, thereby enhancing NO production and inducing vascular relaxation. 94 Furthermore, resveratrol (25-100 mM) prevented the proliferation of vascular smooth muscle cells isolated from SHRs.…”
Section: Effects Of Resveratrolmentioning
confidence: 99%
“…92 In addition, 0.0% resveratrol exerts a marginally inhibitory effect on serum IL-1β and monocyte chemotactic protein 1 levels, which are involved in inflammation in SHRSP. 93…”
Section: Introductionmentioning
confidence: 99%